COMPARISON OF OPPORTUNITIES OF LARGE-ORBIT gyro-TWT AND peniotron ON MODE H41 - S. V. Kolosov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of the comparison in terms of efficiency, the band gain, the gain and the initial angular spread of the electron velocities for large-orbit gyro-TWT and peniotron amplifier are given. It is shown that the peniotron amplifier has a higher efficiency and power compared with large-orbit gyro-TWT, but has a narrower band of amplification.